Structured object-oriented formal language and method : 4th International Workshop, SOFL+MSVL 2014, Luxembourg, Luxembourg, November 6, 2014, Revised selected papers /: 4th International Workshop, SOFL+MSVL 2014, Luxembourg, Luxembourg, November 6, 2014, Revised selected papers. (2015) - Unknown
No abstract available